Muscle activation and intermuscular coordination adaptations to early strength training during maximal force production - Paulo D. G. Santos; João R. Vaz; Miguel Gomes; Jorge Infante; Pedro Pezarat-Correia (PLoS ONE, 2026)
Previously untrained individuals tend to increase maximal and rapid strength during the initial resistance training stages. Muscle activation and coordination are neural mechanisms contributing to the increased mechanical output. However, how the force production characteristics are accompanied by changes in activation of agonist muscles as well as coordination of muscles with different functional roles is not fully understood. This study investigated the time course of adaptations following 6 weeks of resistance training, evaluating every two weeks a leg-press isometric maximum voluntary contraction. Peak force (PF), rate of force development (RFD), rate of EMG rise (RER) of the agonist muscles and intermuscular coherence between synergist or antagonist pairs of muscles were evaluated. In result of a dynamic squat program, the maximal and rapid leg-press isometric force increased after the 6-week period ( p = 0.011 and p = 0.015, respectively), although improvements at specific intervals of RFD at specific time points were observed. Regarding knee extensor activation, generally decreased RER was observed only for rectus femoris and not for the monoarticular portions of quadriceps. Additionally, intermuscular coherence analysis revealed increased coupling between rectus femoris and the monoarticular portions of quadriceps after training, and adaptations between agonist muscles acting in different joints as well as between agonist and antagonist muscle at specific time points were observed concerning specific bands. This is the first study to characterize the time course of intermuscular coordination adaptations during the early phase of strength training in previously untrained individuals, bringing new insights into the neural mechanisms of muscle recruitment following resistance training in what concerns to coordinative strategies in the control of muscles with different functional roles.